2021
DOI: 10.3390/vaccines9030287
|View full text |Cite
|
Sign up to set email alerts
|

Perception of COVID-19 Vaccination Amongst Physicians in Colombia

Abstract: Introduction: The SARS-CoV-2/COVID-19 pandemic has triggered the need to develop rapidly effective and safe vaccines to prevent infection, particularly in those at-risk populations such as medical personnel. This study’s objective was to assess the perception of COVID-19 vaccination amongst Colombian physicians featuring two different scenarios of COVID-19 vaccination. Methods: A cross-sectional analytical study was carried out through an online survey directed at medical staff in several cities in Colombia. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
1
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 39 publications
3
33
1
7
Order By: Relevance
“… 20 The finding of the study was higher than the findings in Pakistan (37.80%), 42 Ethiopia (46.1%), 48 Ethiopia (31.4%), 49 16 countries across the continent (52.0%), 50 Nigeria (50.2%), 51 USA (36%), 52 Ethiopia (45.5%), 23 Turkey (29.2%). 53 On the contrary, it was lower than the finding in Canada (80.9%), 54 Mexico and India (80%), 50 China (91.3%), 36 Italy (67%), 55 low and middle-income countries (76.4%), 56 Colombia (77.0%), 57 India (78.6%), 28 India (79%), 44 Bangladesh (74.5%). 58 The low prevalence of vaccine acceptance may be due to the fact that the novelty COVID-19 disease.…”
Section: Discussionmentioning
confidence: 78%
“… 20 The finding of the study was higher than the findings in Pakistan (37.80%), 42 Ethiopia (46.1%), 48 Ethiopia (31.4%), 49 16 countries across the continent (52.0%), 50 Nigeria (50.2%), 51 USA (36%), 52 Ethiopia (45.5%), 23 Turkey (29.2%). 53 On the contrary, it was lower than the finding in Canada (80.9%), 54 Mexico and India (80%), 50 China (91.3%), 36 Italy (67%), 55 low and middle-income countries (76.4%), 56 Colombia (77.0%), 57 India (78.6%), 28 India (79%), 44 Bangladesh (74.5%). 58 The low prevalence of vaccine acceptance may be due to the fact that the novelty COVID-19 disease.…”
Section: Discussionmentioning
confidence: 78%
“…The rates of acceptance among healthcare workers in South American countries were fairly high (from 77% and above in Colombia [88] and 80.7% in Brazil [89] ). Finally, studies assessing willingness to pay for the vaccine were conducted in Chile, and the reported acceptance rates were 83% and 90% [ 90 , 91 ] On the other hand, it was estimated that the amount of willingness to pay by Brazilian consumers for a hypothetical SARS CoV-2 vaccine was US$22.18 [89] .…”
Section: Resultsmentioning
confidence: 99%
“…In most of the samples, the age of respondents lies between 25–40 years. Physicians dominate among healthcare workers in most of the studies (n=13), typically from France, 41 Egypt, 47 Ghana, 48 Congo, 33 Greece, 45 Italy, 44 Poland, 32 Saudi Arabia, 36 Romania, 29 Colombia, 12 Slovenia 34 and the United Arab Emirates. 42 However, nurses dominate among studies conducted in Nepal, 46 Belgium, 35 the USA, 40 Canada, 38 and Saudi Arabia.…”
Section: Resultsmentioning
confidence: 99%
“… 11 In other respects, in terms of vaccine effectiveness, the study showed that between 77.0 and 90.7% of screened physicians in Colombia would accept vaccination against COVID-19 when the vaccine efficacy was 60 and 80%, respectively, at the time when Sinovac (Beijing, China) (Coronavac) and Pfizer-BioNTech (BNT162b2) vaccines types have reported 50% and 95% efficacy. 12 …”
Section: Introductionmentioning
confidence: 99%